Model Pemanfaatan Teknologi Digital di Pesantren - Yuliani, Zahra; Amala, Muhammad Ahsanu; Safira, Tasya; Pratiwi, Khairunnisa (Education Management: Jurnal Manajemen Pendidikan Islam, 2023)
Digital technology in boarding schools is needed to support the learning process and develop the potential of students. There are already many Islamic boarding schools that apply digital technology. However, there are people who consider that digital technology in Islamic boarding schools is still lagging behind, so there is a lack of interest of new students and parents in Islamic boarding schools that are considered outdated and old-fashioned compared to other educational institutions. The purpose of this study is useful to determine the progress of boarding schools that have implemented digital systems in their education management compared to boarding schools that have not implemented digital systems in their education management. Researchers also provide information on how effective the boarding school is in implementing its digital system. Research in the form of descriptive qualitative. Data collection through filling out questionnaires distributed to students who have experienced digital technology in their pesantren. The results showed that many Islamic boarding schools have implemented digital-based systems such as teacher and student attendance with fingerprints, barcodes for borrowing books, payments using e-wallets that have been systematized so that when the payment date appears notification to parents, create a website for student activities while in the Islamic boarding school and can be seen by parents. The digital system in pesantren has developed so that Many Islamic boarding schools have used digital systems in all fields of activity and learning, this is very helpful for Islamic boarding schools to develop and compete with other educational institutions